Praktik Judicial Activism dalam Putusan Mahkamah Konstitusi Dikaitkan dengan Prinsip Pemisahan Kekuasaan - Arrasuli, Beni Kharisma; Nadhilah, Yumni (UNES Law Review, 2023)
The Constitutional Court is one of the perpetrators of the Judicial Power who performs the judicial function in Indonesia. One of the authority of the Constitutional Court is to examine the law against the Basic Law, this was born based on the principle of separation of powers and protection of human rights. Constitutional Court Judges have the freedom to interpret the Constitutional norms based on the independence of the Judicial Power. Interestingly, the Constitutional Court often issues controversial decisions because the Constitutional Court Judges apply the doctrine of judicial activism in their decisions. Judicial activism is a philosophy of making court decisions by putting forward the personal views of judges as a basis for consideration so that constitutional norms are interpreted beyond contextual provisions. So that Constitutional Court judges tend to make laws (judge making law) through decisions that should be the realm of legislators. The questions in this paper are: First, how is the practice of judicial activism in the Constitutional Court judge's decision. Second, what are the implications of the practice of judicial activism in the Constitutional Court's ruling on the principle of separation of powers? The writing of this article uses the method of normative legal research through a legal, historical and conceptual approach to answer whether there is a regulation that prohibits judges from the Constitutional Court to practice judicial activism. Furthermore, can this be said as strengthening the role of the Constitutional Court in creating a mechanism of checks and balances on the House of Representatives as a branch of legislative power that functions as a legislator in the system of separation of powers in Indonesia.